Sodium butyrate mediates histone crotonylation and alleviated neonatal rats hypoxic–ischemic brain injury through gut–brain axis - He, Xuejia; Zhang, Ting; Zeng, Yubing; Pei, Pei; Liu, Yulan; Jia, Wenbin; Zhao, Hongyang; Bi, Meirong; Wang, Shan (Frontiers in Microbiology, 2022)
Neonatal hypoxic-ischemic encephalopathy (HIE) refers to nervous system damage caused by perinatal hypoxia, which is the major cause of long-term neuro-developmental disorders in surviving infants. However, the mechanisms still require further investigation. In this study, we found that the butanoate metabolism pathway exhibited significantly decreased and short chain fatty acid (SCFAs)-producing bacteria, especially butyrate-producing bacteria, were significantly decreased in fecal of neonatal hypoxic-ischemic brain damage (HIBD) rats. Surprisingly, Sodium butyrate (SB) treatment could ameliorate pathological damage both in the cerebral cortex and hippocampus and facilitate recovery of SCFAs-producing bacteria related to metabolic pathways in neonatal HIBD rats. Moreover, we found that in samples from SB treatment neonatal HIBD rats cortex with high levels of butyrate acid along with aberrant key crotonyl-CoA-producing enzymes ACADS levels were observed compared HIBD rats. We also demonstrated that a decrease in histone 3-lysine 9-crotonylation (H3K9cr) downregulated expression of the HIE-related neurotrophic genes Bdnf, Gdnf, Cdnf, and Manf in HIBD rats. Furthermore, SB restored H3K9cr binding to HIE-related neurotrophic genes. Collectively, our results indicate that SB contributes to ameliorate pathology of HIBD by altering gut microbiota and brain SCFAs levels subsequently affecting histone crotonylation-mediated neurotrophic-related genes expression. This may be a novel microbiological approach for preventing and treating HIE.